Efficacy of in situ active capping Cd highly contaminated sediments with nano-Fe2O3 modified biochar. (1st December 2021) - Liu, Qunqun; Sheng, Yanqing; Liu, Xiaozhu
Abstract: Effective remediation of Cd polluted sediment is imperative for its potential damages to aquatic ecosystem. Biochar (BC) and nano-Fe2 O3 modified BC (nFe2 O3 @BC) were conducted to remedy Cd highly contaminated sediments, and their performances, applicable conditions, and mechanisms were investigated. After 60 d capping, both BC and nFe2 O3 @BC capping inhibited Cd release from sediment to overlying water and porewater (reduction rates >99%). The released Cd concentrations in overlying water with nFe2 O3 @BC capping decreased by 1.6–11.0 times compared to those of BC capping, indicating nFe2 O3 @BC presented a higher capping efficiency. Notably, the increases of acidity and disturbance intensity of overlying water weakened the capping efficiencies of nFe2 O3 @BC and BC. BC capping was inappropriate in acidic and neutral waters (pH 3, 5, and 7) because Cd maintained a continuous release after 15 d, while nFe2 O3 @BC capping was valid in all pH treatments. Under 150 rpm stirring treatment, Cd release rates with BC and nFe2 O3 @BC capping decreased after 15 d and 30 d, respectively. At 0 and 100 rpm treatments, Cd releases treated by nFe2 O3 @BC capping finally kept a balance, indicating nFe2 O3 @BC was valid at low disturbance intensity. BC and nFe2 O3 @BC capping inhibited Cd release via weakening the influences of pH and disturbance on sediment. However, capping layers should be further processed because most adsorbed Cd in capping layers (>98%) would be re-released into overlying water. Meanwhile, excessive application of nFe2 O3 @BC could increase the risk of Fe release. The results provide novel insights into the potential applications of nFe2 O3 @BC and BC in situ capping of Cd polluted sediments in field remediation. Highlights: BC and nFe2 O3 @BC capping greatly reduced Cd release from sediments. BC capping was only applicative in alkaline water body. nFe2 O3 @BC capping availability was affected by disturbance intensity not by pH. Excessive application of nFe2 O3 @BC capping could increase the risk of Fe release. Capping layers should be further processed due to most adsorbed Cd was unstabl.